Online Gambling in Indonesia: User Intention Factors Analysis - Alwafi, Muhammad Ashfahani; Purwandari, Betty; Satria, Riri; Trimanadi, R. (International Journal of Advances in Data and Information Systems, 2026)
The rapid growth of online gambling posed a serious socio-economic threat in Indonesia, with transaction values reaching hundreds of trillions of rupiah. This study aimed to analyze the factors influencing the intention to engage in online gambling by integrating the Theory of Planned Behavior (TPB) with contextual external variables. Data were collected through a questionnaire from 187 Indonesian respondents with online gambling experience and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicated that online gambling intention was significantly and directly influenced only by perceived behavioral control and monetary gain. Furthermore, religiosity played a significant indirect role by strengthening perceived behavioral control, which in turn affected intention. The findings suggested that intervention strategies should extend beyond awareness campaigns to include targeted financial literacy education and the reinforcement of regulatory and technological barriers to disrupt the perceived ease and financial allure of gambling platforms.